VIOLÊNCIA ENTRE PARCEIROS ÍNTIMOS E BAIXO PESO AO NASCER - Raquel de Souza Mezzavilla (Universidade do Estado do Rio de Janeiro, 2014)
Children with low birth weight (LBW) have higher risk of illness and death throughout life. Recentstudies on risk factors for LBW relates specifically to the role of maternal psychosocial factors such asstress, lack of social support and partner, a time for unity and conflict between the couple. Investigationson the association between intimate partner violence (IPV) and LBW are relatively scarce and reportingcontroversial results. The aim of this study is to investigate the association between IPV and the occurrenceof LBW. This is a cross-sectional study with 626 infants born to women who attended the four health facilitiesin the municipality of Rio de Janeiro, between June 2005 and December 2009. Information regardingthe VPI were obtained by the Portuguese version of the instrument CTS-1 (Conflict-tatics Scales Form R)(Hasselmann & REICHENHEIM, 2003) in the first month of life of the child. The IPV was analyzed asdichotomous and cumulative. Two outcomes were studied: low birth weight (weighing less than 2500 g) andterm LBW (weight less than 2500 g born at 37 weeks gestation or more). Associations were verified via logisticregression models, using estimates of odds ratios (OR) and confidence intervals of 95% (95%). In multivariateanalysis, associations between IPV and the outcomes of interest (LBW and term LBW) were adjusted by thecovariates whose associations with the outcome had a significance level less than or equal to 10% in crudeanalysis (p-value ≤ 0.1). Low birth weight and LBW at term 7.2% and 4.8% of children respectively and33.5% of the women studied were exposed to IPV. In multivariate analysis, the presence of physical violencebetween intimate partners was significantly associated with LBW [OR = 4.26; (95%) = 1.69 to 10.68] andterm LBW [OR = 5.90 ; (95%) = 1.65 to 21.02]. It is noteworthy that as the severity of violence continuesto grow, the chances of low birth weight [OR = 3.61; (95%) = 1.19 to 10.97] and [OR = 4.99 ; (95%) =1.70 to 14.65], regardless of maternal age and education, smoking, parity, weight gain during pregnancy,hypertension, social networking, social support, environmental conditions and sex of the child As for lowbirth weight at term, although the association with cumulative violence is significant, did not show thisbehavior. Conclusion: These findings call attention to the consequences of intimate partner violence forchild's health, and highlight the need to support pregnant women exposed to violence, as well as greaterattention during prenatal care in order to reduce births low birth weight. DOI 10.12957/demetra.2014.10830